Bank Organizational Structure Choice Dilemma. Case of PKO BP - Adam Szafarczyk (Contemporary Economics)
Organizational structures are differing for different banks. They depend on individual bank economic situation, its technology, strategy and form of competition struggle. Usually the biggest EU banks are consists from formally or really independent divisions. The most common divisions are Retail Banking, Corporate Banking, Treasury and Investment, sometimes Insurance. PKO BP, the biggest Polish Bank, ought to change its structure due to implementation new IT system.